1996
DOI: 10.1080/00071669608417871
|View full text |Cite
|
Sign up to set email alerts
|

Effects on dietary phosphorus of treating cottonseed meal with crystalline ferrous sulphate for the prevention of brown yolk discolouration

Abstract: 1. Two experiments were carried out to examine whether the adverse effects on laying hen performance of treating cottonseed meal (CSM) with crystalline ferrous sulphate heptahydrate (FSH) to prevent brown yolk discolouration, was a consequence of iron reducing the availability of dietary phosphorus. Two batches of CSM, with different free gossypol and cyclopropenoid fatty acid contents, were treated with FSH at a 4:1 weight ratio of iron to free gossypol, and incorporated into diets at 300 g/kg with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
1
12
0
1
Order By: Relevance
“…Egg weight was reduced by the exposure to free gossypol in the feed at 255 mg/kg (Panigrahi et al, 1989). Other described adverse effects of gossypol exposure are discoloration of the egg yolk and/or of the albumen (Panigrahi et al, 1989;Panigrahi & Hammonds, 1990;Panigrahi, 1992;Panigrahi & Plumb, 1996;Lordelo et al, 2007). The results of the present study evidence that the reported effects of gossypol on egg production and egg quality may be due to its direct damage of the ovaries.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Egg weight was reduced by the exposure to free gossypol in the feed at 255 mg/kg (Panigrahi et al, 1989). Other described adverse effects of gossypol exposure are discoloration of the egg yolk and/or of the albumen (Panigrahi et al, 1989;Panigrahi & Hammonds, 1990;Panigrahi, 1992;Panigrahi & Plumb, 1996;Lordelo et al, 2007). The results of the present study evidence that the reported effects of gossypol on egg production and egg quality may be due to its direct damage of the ovaries.…”
Section: Discussionsupporting
confidence: 63%
“…In laying hens fed cottonseed, gossypol was found to reduce egg production (Fitzsimmons et al, 1989;Panigrahi et al, 1989) and egg weight (Panigrahi et al, 1989), and to cause discoloration of the egg yolk and/or albumen (Panigrahi et al, 1989;Panigrahi & Hammonds, 1990;Panigrahi, 1992;Panigrahi & Plumb, 1996;Lordelo et al, 2007). The complete cessation of egg production may occur (Fitzsimmons et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The toxic effects of gossypol may be alleviated by supplementation of soluble iron salts that bind gossypol (Panigrahi and Morris, 1991). However, it is costly and can depress bird performance by reducing the availability of dietary phosphorus (Panigrahi and Plumb, 1996). Small reduction in gossypol content of cottonseed by gamma irradiation at a dose level of 10 kGy has been observed (Abu-Tarboush, 1998), but no information is available on the effects of higher doses of gamma rays and especially electron beam irradiation to reduce gossypol to the permissible level.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reduction of gossypol using solvents suffers from the difficulty of totally removing residual solvents that may be potentially harmful to the animals. Chemical detoxification are achieved by addition of ferric sulfate, alkali, and other chemical reagents into CSM to form complexes with FG, but the obvious deficiency is the residual of these ingredients (Panigrahi and Plumb 1996;Nagalakshmi et al 2002). In our previous research, 10 mL of FeSO 4 , NaOH, Ca(OH) 2 , H 2 O 2 , and urea solutions (at the concentration of 1.5 %) was added into 5 g of CSM separately to decrease FG content.…”
Section: Introductionmentioning
confidence: 99%